Baseline assessment of age-friendliness for Taiping - Ahmad, Siti Anom; Hui, Foh Foong; Abdullah, Siti Farra Zillah; Chai, Sen Tyng; Ibrahim, Rahimah; Syed Abdul Rashid, Sharifah Norazizan; Ismail, Sumarni; Hamid, Tengku Aizan (Faculty of Medicine and Health Sciences, 2022)
Among the states in Malaysia, Perak is the “oldest” state with 14.9% of its population aged 60 and above in 2020. The aim of this work is to promote public participation in local planning to develop an action plan with the aim of creating an environment that age-friendly in Taiping. Baseline assessment was conducted through online survey. 1,114 responses were analysed. Result shows the mean score of perceived age-friendliness level in Taiping is 53, means moderate. Age-friendly environment is already present in Taiping and the local council needs to select an urgent age-friendly domain to address in the immediate future.